The Effect of Discovery Learning Assisted Powerpoint on the Learning Motivation and Mathematics Learning Outcomes - Alfrida Mambaya; Abdul Rahman; Suroyo Suroyo (EduLine: Journal of Education and Learning Innovation, 2022)
The purpose of the research to analize discovery learning and powerpoint effect on the learning motivation and mathematics learning outcomes. This research uses a quantitative approach with pre-experimental design model one group pretest-posttest. The population and sample in this study were all students of class VI SDN 1 Rantepao. Total of population is 53 student diveded in two classes and to get sample uses cluster random sampling technique. The sample is 26 students at the VIB Class. Based on the results for learning motivation with t test, it was obtained the value of Sig. (2-tailed) 0.01 < 0.05 which indicates that discovery learning has a significant effect on learning motivation. The t-test for learning outcomes obtained skog sig(2 tailed) 0.000 <0.05 which indicates that there is a significant effect of the use of discovery learning on student learning outcomes